The Weathercock: Being the Adventures of a Boy with a Bias - Fenn, George Manville, 1831-1909; Cooper, Alfred W. (Salt Lake City, UT : Project Gutenberg, 2007)
"The Weathercock: Being the Adventures of a Boy with a Bias" by George Manville Fenn is a novel likely written in the late 19th century. This story follows the adventures of Vane Lee, a clever and inventive sixteen-year-old boy who lives with his uncle, a doctor, in a quaint Lincolnshire village. Vane's interests encompass naturalism and invention, leading him into various escapades and conflicts, particularly with a fiery fellow student named Lance Distin. The opening of the book introduces Vane as he collects edible fungi on a sunny morning, showcasing his character through interactions with friends and rivals. After a humorous incident involving a church clock he attempted to fix, the narrative quickly escalates into more serious territory when he faces a confrontation with gipsy boys and eventually an ill-fated boating adventure with Distin and others. This segment sets the tone for Vane's inventive spirit while foreshadowing underlying tensions, particularly with Distin, which promise to drive further conflict as the story unfolds. (This is an automatically generated summary.)
Release date is 2007-05-08
Produced by Nick Hodson of London, England
Keywords: Young men -- Conduct of life -- Juvenile fiction; Friendship -- Juvenile fiction; England -- Social life and customs -- 19th century -- Juvenile fiction; Inventions -- Juvenile fiction; Romanies -- Juvenile fiction